The Influence Of Independence And Time Pressure On Auditors' Ability Detect Financial Statement Fraud With Professional Skepticism As A Moderating Variable - Sabilla Luthfiannisa Agustin; Luqman Hakim (EKOMBIS REVIEW: Jurnal Ilmiah Ekonomi dan Bisnis, 2025)
Introduction: Financial statement fraud is a serious issue that can undermine the integrity of financial information and public trust. Therefore, understand the factors that influence auditors' ability detect such fraud. Research Methods: This research uses a quantitative approach with a survey method. The sample non-probability sampling used purposive sampling, data auditors working in Public Accounting Firms in South Jakarta. Analyzed using of SmartPLS ver. 4.1 software. Results: Time pressure has a positive effect on auditors' ability detect financial statement fraud, while independence has not effect. Professional skepticism also has a positive effect on auditors' ability detect fraud. However, professional skepticism weakens the relationship between independence and time pressure on auditors' ability detect financial statement fraud. Conclusion: Time pressure and professional skepticism are important factors influencing auditors' ability to detect financial statement fraud. However, while independence has not effect. Professional skepticism also weakens the relationship between independence and time pressure with auditors' ability to detect fraud.